2018
DOI: 10.4236/jmp.2018.914165
|View full text |Cite
|
Sign up to set email alerts
|

Water Memory Due to Chains of Nano-Pearls

Abstract: Biologically active molecules create substitutes in liquid water by forming single-domain ferroelectric crystallites. These nanoparticles are spherical and constitute growing chains. The dipoles are aligned, but can be set in oscillation at the frequency of vibration of the charged part of active molecules. They are then automatically trimmed and become information carriers. Moreover, they produce an oscillating electric field, causing autocatalytic multiplication of identical chains in the course of successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…First, the homeopathic potency is capable of self-organizing and inducing formation of self-similar nano-structures in surrounding water. 5,8,[20][21][22][23][24][25][26][27] Second, multiple studies of plants have shown that homeopathic potencies induce formation of self-organized, unique poly-crystalline structures in the exudates of treated plant seedlings versus controls. 6,7,28,29 In other words, homeopathically prepared medicines may induce formation of self-similar crystalline nano-structures in water and/or in biological fluids within a living system.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the homeopathic potency is capable of self-organizing and inducing formation of self-similar nano-structures in surrounding water. 5,8,[20][21][22][23][24][25][26][27] Second, multiple studies of plants have shown that homeopathic potencies induce formation of self-organized, unique poly-crystalline structures in the exudates of treated plant seedlings versus controls. 6,7,28,29 In other words, homeopathically prepared medicines may induce formation of self-similar crystalline nano-structures in water and/or in biological fluids within a living system.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
“…8 Furthermore, multiple research groups have reported evidence that homeopathic manufacturing induces persistent formation of electromagnetic signal-induced, self-organized crystalline water nano-structures, termed "dissipative structures" by Elia et al, 8,76,77 "nano-associates" by Konovalov et al, 20,21 or "nano-pearls" (poly-crystals formed of many microscopic crystallites) by Meessen. 5 Crystalline structures at the nano-scale (or larger) spontaneously self-organize from an interaction of their constituent parts with each other and with their environment.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This two-part paper focuses on the integrative model for the complex, self-organizing nature of both (1) recipient living systems [1][2][3][4] and (2) homeopathic medicines [5][6][7][8][9][10] as the basis for homeopathic healing. In Part 1, we review how complex systems science applies to homeopathic clinical concepts and the non-linear, system-wide healing response that simillimum treatment initiates.…”
Section: Introductionmentioning
confidence: 99%
“…Since this concerns condensed matter physics, we tried to solve this problem and published in 2018 a rational explanation [84]. Since water molecules are dipolar, they can constitute very dense crystallites, where all these dipoles have the same orientation.…”
Section: Discussionmentioning
confidence: 99%